Elite male 400m hurdle tactics are influenced by race leader - Greene, D.; Leyshon, W.; O'Donoghue, P. (World Congress of Performance Analysis of Sport VIII, 2008)
On average, men and women`s speed was found to decrease throughout the course of the race. These results agree with those of Linderman (1995), Ditrolio and Marini (2004) as well as the results of Pendergast`s (1991) case study of Andre Philips` 1988 Olympic final performance. All three of the performance indicators show greater percentage increases for the women compared to the men. Although differences can be seen between the genders, only the results for PI1 was found to be significant. Women have a significantly greater percentage increase in time for the second half of the race, when compared to the first half, than men. A possible explanation of this is that the 400m is a newer event for women than it is for men (Breizer and Korchemny 1993). The importance of %increase in time between the first and second halves of the race for men is supported by Ditrolio and Marini`s (2004) study where the best performances came from those athletes who had the lowest difference between the second half of the race compared to the first. The correlations between elapsed times to hurdles and the overall race time are higher for men than for women, meaning that better predicition of race time can be made for men`s performances based on time trials of 7 hurdles or more than can be made for women`s performances. This is supported by Yasui et al.`s (1996) study that found that the time between hurdle 6 and hurdle 7 was the most correlated hurdle split time with overall race performance. The current results suggest that in men`s 400m hurdles races, the tactics of athletes is influenced by what the activity of early race leaders. An explanation of this is that world class athletes are better judges of race pace and are more confident allowing early leaders to move ahead where it is unrealistic to maintain the pace set. This study proposed performance indicators for the 400m hurdles event that could be used for both male and female 400m hurdlers. The most noticeable findings from this study were that Time to hurdle 7 can be used as a predictor of overall race time in men`s races. Female athletes start relatively faster than men do. In future studies, it would be useful to look at a greater number of subjects, especially female subjects. Areas for future investigations include analysing the effect of changedown for different levels of athlete and an intervention study to analyse the effectiveness of using the performance indicators within the coaching of 400m hurdlers.